Structure and composition of yellowtail kingfish ( Seriola lalandi ) otoliths: implications for using aquaculture‐reared fish to reconstruct life histories - Belinda K. Goddard; Laura M. Otter; Julian M. Hughes; Fabrice R. A. Jaine; Jasmin C. Martino; Ulrike Troitzsch; Jackson Doherty; Hayden T. Schilling (Journal of Fish Biology, 2025)
Understanding fish life history is essential for effective management of fisheries, but continuous tracking over lifetime temporal scales can be difficult. Fish otoliths contain a natural biogeochemical record of ambient environmental conditions and habitat use over such scales. However, ecological interpretations of these elemental compositions can be influenced by the structural composition of calcium carbonate otoliths, which can vary between wild and aquaculture fish as well as across species. As such, we used in situ confocal micro‐Raman spectroscopy and powder X‐ray diffraction to assess and quantify, respectively, the calcium carbonate polymorphs of the otoliths of aquaculture and wild yellowtail kingfish ( Seriola lalandi ) to validate whether the otoliths from aquaculture fish can be used to interpret patterns seen in the otoliths of wild fish. We then analysed major and minor trace elements using wavelength dispersive X‐ray spectroscopy to investigate the potential habitat use of wild S. lalandi . The elemental composition of S. lalandi otoliths was examined across three cross‐sectioned growth zones: the first (i.e. oldest) annulus (growth ring), the outermost (i.e. most recent) annulus and mid‐way between these. All otoliths were shown to be composed of aragonite, with the exception of small proportions (0.5 wt%) of vaterite in a single wild S. lalandi otolith. This finding indicates that otoliths of aquaculture S. lalandi , reared in known conditions, are appropriate to interpret stable isotope analyses in wild S. lalandi . Wild‐caught S. lalandi otoliths had concentrations of barium and manganese below detectable limits ( S. lalandi were not in estuarine or brackish environments when the analysed annuli were formed, suggesting these environments are not used for spawning.

A synoptic climatology of strong along‐channel winds on the Coast of British Columbia, Canada - Talaat Bakri; Peter Jackson; Ford Doherty (International Journal of Climatology, 2017)
A synoptic climatology using mean sea level pressure and 500‐ hPa geopotential height composites is conducted for strong along‐channel winds that occur through five of the channels dissecting British Columbia's coast. Seasonal (winter, summer) and directional (inflow, air moving from the coast inland; outflow, air moving from inland towards the coast) partitioning of the winds, results in four distinct along‐channel winds that occur: summertime inflow, summertime outflow, wintertime inflow and wintertime outflow. Composite analyses using reanalysis data and in situ observations are used to examine each wind type at all locations. Wintertime composites produce patterns that are distinct from the overall winter climatology, in which outflows occur when an arctic surface high‐pressure area on the inland side of the coastal mountains is accompanied by the presence of an area of low surface pressure in the northeastern Pacific. Inflow composites in the winter indicate low‐pressure areas associated with mid‐latitude cyclones over the Gulf of Alaska. Summertime composites are similar to the overall summer climatology; therefore, other approaches are applied to explain these winds. We analyse 104 summertime inflow events at three locations using surface analysis charts for 13 summer seasons. The analysis reveals the importance of fronts at the time of inflows, with fronts associated with almost half of the events. Non‐hierarchical clustering analysis is applied for the summertime inflow events. The clustering analysis gives a better explanation of the summertime inflows than the composites. This is achieved by grouping events into different clusters, allowing for better illustration of the variance between the clusters.